Building a framework of security for Southeast Europe and the Black Sea region : a challenge facing NATO - Peterson, James W. (James Walter), 1945- (The Edwin Mellen Press, 2013)
Security issues in Southeast Europe are tricky because the region has been in turmoil for many years. North Atlantic Treaty Organization (NATO) stands out as a likely counterweight to the local problems that have plagued the region, and could serve as a stabilizing force. The book focuses on counter-terrorism measures that can be taken in Southeast Europe, specifically by NATO allies in the region. NATO has played an important role in Southeast Europe in the post-Cold War years. Their brief and selective bombing operation in 1995 helped bring the Bosnian War to a conclusion and the participant.